2010
DOI: 10.1590/s1984-29612010000300009
|View full text |Cite
|
Sign up to set email alerts
|

Amblyomma rotundatum (Koch, 1844) (Acari: Ixodidae) two-host life-cycle on Viperidae snakes

Abstract: Amblyomma rotundatum is an ixodid tick that infests ectothermic animals and reproduces exclusively by parthenogenesis. This tick has been frequently reported to infest reptiles and amphibians, under natural conditions and sometimes in captivity. It was described in Brazil and several other countries of South, Central and North America. Although many studies have reported aspects of its biology, none of them has used regularly either ophidian as hosts, or controlled temperature, humidity and luminosity for para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The bioecology of this species under quasi-natural environment demonstrated a peak of larvae and nymphs in the dry season and females in the rainy season; however, there is a hypothesis of the absence of seasonality in this tick [48,49]. Although A. rotundatum is a three-host tick on amphibians, it can behave as a two-host tick when feeding on snakes [50]. The complete experimental life cycle, including preattachment periods for each parasitic stage, ranged from 126 to 228 days on toads [51] or 56 to 163 days on snakes [50] and ulcerative lesions and hemorrhages after A. rotundatum feeding [48] were reported for ticks collected on toads from the Cerrado biome.…”
Section: Hard Ticks Associated With Amphibians and Reptilesmentioning
confidence: 96%
See 1 more Smart Citation
“…The bioecology of this species under quasi-natural environment demonstrated a peak of larvae and nymphs in the dry season and females in the rainy season; however, there is a hypothesis of the absence of seasonality in this tick [48,49]. Although A. rotundatum is a three-host tick on amphibians, it can behave as a two-host tick when feeding on snakes [50]. The complete experimental life cycle, including preattachment periods for each parasitic stage, ranged from 126 to 228 days on toads [51] or 56 to 163 days on snakes [50] and ulcerative lesions and hemorrhages after A. rotundatum feeding [48] were reported for ticks collected on toads from the Cerrado biome.…”
Section: Hard Ticks Associated With Amphibians and Reptilesmentioning
confidence: 96%
“…Although A. rotundatum is a three-host tick on amphibians, it can behave as a two-host tick when feeding on snakes [50]. The complete experimental life cycle, including preattachment periods for each parasitic stage, ranged from 126 to 228 days on toads [51] or 56 to 163 days on snakes [50] and ulcerative lesions and hemorrhages after A. rotundatum feeding [48] were reported for ticks collected on toads from the Cerrado biome. Transmission of the hemogregarine Hemolivia stellata by R. marina collected in Belém, state of Pará was reported by Petit et al [52].…”
Section: Hard Ticks Associated With Amphibians and Reptilesmentioning
confidence: 99%
“…Some tick species have retained a predilection for cold-blooded vertebrates. Amblyomma rotundatum (Koch, 1844) is an ixodid tick that infests ectothermic animals reported to infest reptiles and amphibians (Rodrigues et al, 2010). Ticks are generally of 3 types identified as hard ticks, soft ticks and Nuttalliella (the combination of hard and soft ticks) (Guglielmon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Amblyomma rotundatum Koch is a parthenogenetic tick (ARAGÃO, 1912;OBA;SCHUMAKER, 1983) commonly associated with species of reptiles and amphibians (DURDEN;KNAPP, 2005;PONTES et al, 2009;GUGLIELMONE;NAVA, 2010). Experimental studies have shown that during its life cycle, this species uses two or three different host species (OBA;SCHUMAKER, 1983;RODRIGUES et al, 2010). In addition, ticks can act as vectors of hemoparasites of the genera Hemolivia and Hepatozoon for frogs (PETIT et al, 1990;LAINSON et al, 2007), lizards (SMALLRIDGE;PAPERNA, 1997;PAPERNA et al, 2002) and turtles (PAPERNA, 2006;SIROKÝ et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, except for the broad study by Pontes et al (2009) involving ticks associated with a community of snakes in the Atlantic Forest, most studies have been limited to recording parasitism of reptiles by ticks in random samples, usually restricted to a few individual specimens (LABRUNA et al, 2002(LABRUNA et al, , 2005DANTAS-TORRES et al, 2005MARTINS et al, 2007;LOPES et al, 2010), studies involving captive hosts (see review in GUGLIELMONE; NAVA, 2010), or characterization of the life cycle of ticks Amblyomma dissimile or A. rotundatum under experimental conditions (ARAGÃO, 1912;OBA;SCHUMAKER 1983;FREITAS et al, 2004;RODRIGUES et al, 2010).…”
Section: Introductionmentioning
confidence: 99%